1986
DOI: 10.1203/00006450-198612000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Malnutrition and Chronic Reserpine Treatment on Pancreatic Exocrine Function1

Abstract: ABSTRAm. The chronically reserpine-treated rat, an experimental model for cystic fibrosis, exhibits generalized exocrinopathy, impaired pancreatic secretion, and decreased pancreatic amylase. Although chronic reserpine treatment induces malnutrition by decreasing food consumption and growth, the effects of this malnutrition per se on the exocrine pancreas have not been considered. In this study, the effects of chronic reserpine treatment and malnutrition on the exocrine pancreas were determined using pair-fed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
6
1

Year Published

1987
1987
1996
1996

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 14 publications
4
6
1
Order By: Relevance
“…In contrast, the decreased content of amylase, the increased content of chymotrypsinogen, and the diminution in body wt cannot specifically be attributed solely to reserpine because malnutrition alone could also induce similar effects in the group of pair-fed animals. The latter conclusions are similar to those of Hazlett et al (23) and Webster et al (24), who also observed that decreased levels of amylase and total proteins could be secondary to malnutrition. The increase observed in lipase content, however, was not observed by Hazlett et al (23).…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, the decreased content of amylase, the increased content of chymotrypsinogen, and the diminution in body wt cannot specifically be attributed solely to reserpine because malnutrition alone could also induce similar effects in the group of pair-fed animals. The latter conclusions are similar to those of Hazlett et al (23) and Webster et al (24), who also observed that decreased levels of amylase and total proteins could be secondary to malnutrition. The increase observed in lipase content, however, was not observed by Hazlett et al (23).…”
Section: Discussionsupporting
confidence: 91%
“…This secretion was decreased in the R500, R5, and PFS rats. In a previous study, pancreatic acini from rats treated with 500 /Ig/kg reserpine secrete significantly less amylase in response to cholecystokinin than do acini from control rats, while acini from PFS rats show intermediate secretion between reserpine-treated and control acini (14). In the present study using M carbachol, amylase secretion by acini from PFS rats also tended to be intermediate between that of C and R500 or R5 acini.…”
supporting
confidence: 51%
“…Pancreatic protein and amylase activity are decreased similarly in chronically reserpine-treated and PFS rats (restricted to the food consumption of the chronically reserpinetreated rats), but pancreatic amylase secretion is significantly less in acini isolated from chronically reserpine-treated rats compared to acini from PFS rats. These results indicate that some effects of reserpine, but not all, may be due to the induced malnutrition (14).…”
mentioning
confidence: 74%
See 2 more Smart Citations